Combining self-management cues with incentives to promote interdental cleaning among Indian periodontal disease outpatients. Issue 1 (December 2016) - Lhakhang, Pempa; Hamilton, Kyra; Sud, Nayantara; Sud, Shonali; Kroon, Jeroen; Knoll, Nina; Schwarzer, Ralf
Abstract Background Periodontal disease is a significant public health issue worldwide. Motivational techniques in combination with financial incentives are shown to lead to effective behavior change. The current study sought to examine whether a brief oral health promotion program (self-management cues that were based on self-efficacy and self-regulatory skills) in combination with an incentive (free dental treatment) would make a difference in the adoption of regular dental flossing in a population of Indian periodontal disease outpatients. Methods One hundred and twelve participants (n = 55 oral health promotion intervention group;n = 57 control group) were assigned to the intervention (self-management cues + incentive) or control groups, and follow-up assessments were performed three weeks later. Flossing frequency, behavioral intentions, and perceived self-efficacy served as dependent variables. Data were analyzed with mixed models, ANCOVAs, and path analyses. Results The intervention yielded effects on flossing frequency (p < 0.01) and flossing intentions (p < 0.01) at follow-up. Women developed stronger intentions than men. Moreover, by path analysis a sequential mediation chain was found that demonstrated an indirect effect of the intervention on flossing via self-efficacy and intentions: the intervention predicted changes in self-efficacy which, in turn, were associated with changes in intentions, predicting flossing frequency at follow up, while controlling for baseline behavior, gender, and age. Conclusions Combining incentives with minimal self-management cues has been found effective in improving interdental cleaning intentions and habits in periodontal disease patients, and the facilitating role of dental self-efficacy has been demonstrated.